Bacterial pathogens and treatment outcomes in neonatal sepsis: A comparative observational study across various hospital settings - Radhika B,; Vijayasri BSS,; Vidyasagar V,; Jyothi Prakash Raju S, (Asian Journal of Medical Sciences, 2024)
Background: Neonatal sepsis is a leading cause of neonatal morbidity and mortality globally, with variations in causative bacteria and treatment efficacy across health-care facilities. Aims and Objectives: The aims and objectives of the study are to analyze the bacterial pathogens causing neonatal sepsis and the effectiveness of their treatment in diverse hospital environments. By highlighting the differences in treatment success rates, antibiotic resistance profiles, and the pathogens involved, this study demonstrate the impact of health-care practices and infrastructure on the management of neonatal sepsis. Materials and Methods: The study encompassed 100 neonates with sepsis, evenly distributed across the three hospital types. It involved identifying bacterial pathogens through blood cultures, assessing antibiotic sensitivity, and examining treatment outcomes such as success rate, mortality, hospital stay duration, and complication rates. Statistical methods were employed to evaluate differences in outcomes among the settings. Results: Seventy percent of neonates tested positive for bacterial pathogens, with a 60% predominance of Gram-positive over Gram-negative bacteria (40%). Staphylococcus aureus (22%) and Streptococcus agalactiae (18%) were the leading pathogens. Notably, resistance was high against ampicillin (65%) and gentamicin (40%) but lower for cephalosporins and vancomycin. The overall success rate of treatments was 80%, with the tertiary care hospital achieving an 88% success rate, significantly outperforming the private hospitals (72%). The mortality rate was 10%, and 30% of the cases developed complications, predominantly respiratory distress syndrome. Conclusion: Hospital setting significantly influences the management and outcomes of neonatal sepsis, with tertiary care centers showing better results. These findings highlight the need for focused antimicrobial stewardship and the adoption of sophisticated care protocols in less advanced settings to improve neonatal sepsis outcomes.